Pemodelan Dekomposisi Ammonium Carbamate pada Tekanan Tinggi di Pabrik Urea - Sunarya, Rahmat; Sediawan, Wahyudi Budi; Hidayat, Muslikhin (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Urea acts as a nitrogen-based fertilizer to boost crop production and prevent a worldwide hunger crisis. Considering ways to make urea production in existing plants more environmentally friendly, a detailed study has been conducted on the high-pressure stripper, in which the equipment uses intensive energy to decompose ammonium carbamate. The mathematical model was prepared using the two-film theory. The UNIQUAC and Redlich-Kwong equations of state have been used to express nonideality in the NH3-CO2-H2O-urea system under high pressure and temperature circumstances. Due to the lack of transport properties in extreme conditions, the properties were estimated using a theoretical method. The present study obtained the mass-transfer coefficient in dimensionless form  and . Moreover, the heat-transfer coefficient was calculated using the Chilton-Colburn analogy. The proposed model result matches what is expected with the commercial plant data. Furthermore, with less than 5% relative deviations, the model deserves significant consideration for any practical use in high-pressure stripper simulation